Breathable hydrogel dressings containing natural antioxidants for management of skin disorders. (April 2019) - Comotto, Mattia; Saghazadeh, Saghi; Bagherifard, Sara; Aliakbarian, Bahar; Kazemzadeh-Narbat, Mehdi; Sharifi, Fatemeh; Mousavi Shaegh, Seyed Ali; Arab-Tehrany, Elmira; Annabi, Nasim; Perego, Patrizia; Khademhosseini, Ali; Tamayol, Ali
Traditional wound dressings are not effective enough to regulate the moisture content and remove excessive exudate from the environment. Wet wound dressings formed from hydrogels such as alginate are widely used in clinical practice for treatment of skin disorders. Here, we functionalize alginate dressings with natural antioxidants such as curcumin and t -resveratrol to render them both anti-inflammatory and antibacterial. The hydrogel maintains excellent mechanical properties and oxygen permeability over time. The release rate of the compounds from the hydrogels is assessed and their impact on bacterial and cellular growth is evaluated. The antioxidant compounds act as bactericidal agents and improve cell viability. The optimal concentration of active compounds in the engineered alginate-based dressings is determined.